A small university and knowledge-based development: a case of Northern Iceland. (1st January 2014) - Edvardsson, Ingi Runar
The aim of this paper is to outline the progress of the University of Akureyri and its effect on regional development in Northern Iceland during the period of 1987–2012. A case study methodology was used, drawing upon historical material, official sources, and interviews. The main findings are that the university has greatly stimulated knowledge-based development in Northern Iceland. It has enhanced regional innovation dynamism by strengthening human, relational, structural and social capital of the area. This paper has drawn attention to diverse positive effects of a small university with regard to regional- and knowledge-based development. As such, it might serve as a catalyst for further research in this area.